The Effect Of The Implementation Of The E-Filing System, E-Biling, E-Spt And Tax Sanctions On The Compliance Of Individual Taxpayers Registered At The Pratama KPP Of Bengkulu Two - Ahmad Junaidi; Ateri Dendi (UNIVED Press, 2025)
This study aims to look at the effect of the application of the e-filing system, e-billing, e-spt and tax sanctions on the compliance of individual taxpayers registered at Kpp Pratama Dua. This study uses quantitative methods of primary data, data collection methods using questionnaires. The population in this study were all individual taxpayers registered at KPP Pratama Bengkulu Dua which amounted to approximately 83,059 people. This study uses purposive sampling technique. The sample used in this study amounted to 399 individual taxpayers as respondents. The calculation is obtained from the Slovin Formula calculation formula. The data analysis technique uses SPSS 26 (Statistical Product & Services Solution). The results showed that e-filing has a positive effect on individual taxpayer compliance, e-billing has a positive effect on individual taxpayer compliance, e-spt has a positive effect on individual taxpayer compliance and tax sanctions have a positive effect on individual taxpayer compliance.